Assessment and management of chronic oncologic pain in a pediatric inpatient unit - Thiago Privado da Silva; Laura Johanson da Silva; Ítalo Rodolfo Silva; Maria José Carvalho Ferreira; Luana dos Santos Costa; Joséte luzia Leite (In Memorian) (Universidade Federal de Santa Maria, 2021)
Objective: to understand the complexity of the assessment and management of chronic oncologic pain in hospitalized children. Method: qualitative study based on Complexity Theory and Grounded Theory. A total of 21 health professionals participated in the research. Semi-structured interview and non-participant observation were used to collect the data. The analysis followed the coding steps. Result: the pain assessment performed by professionals is based on the relative's report, the child's report and the observation of the child's behavior. Analog color scale, face scale and numerical scale were used. Pharmacological analgesia is the medical prescription; and, in non-pharmacological, ludic aspects, conversation, massage, bathing, warm or cold compress and comfort promotion are performed. Conclusion: the assessment and management process of chronic oncologic pain in hospitalized children requires that health professionals have technical and scientific preparation to deal with objective and subjective aspects that involve this care.